Adoption of Green Finance in Nepal: Perspectives from Employees in Commercial Banks - Ojha, Deepak; Adhikari, Sujita; Ghimire, Rabindra; Subedi, Sabina (Journal of Interdisciplinary Studies, 2026)
Green finance has developed as an emerging concept to enhance sustainable development through environmentally responsible financial activities. Despite increasing regulations and development of green finance facilities in Nepalese commercial banks, little evidence is provided on what factors influence employees’ use of green finance in Nepalese commercial banks. This study intends to identify determinants of adopting green finance in Nepalese commercial banks based on green finance awareness, bank level initiative, regulatory framework and behavioral intention. The research uses quantitative approach with descriptive and explanatory survey design. A structured questionnaire was distributed among 160 employees working in 20 commercial banks at Pokhara Valley. Data analysis was done using descriptive statistics, correlation analysis and multiple regression analysis. The findings of this study shows that green finance awareness, initiatives taken by banks, regulatory framework and behavioral intention have a strong positive correlation with green finance adoption. Bank initiatives are the best predictor followed by green finance awareness while regulation and behavioral intention also have significant positive relationship. However, lack of employee training and awareness on green finance are reported to be the challenges faced by the employees. Thus, providing employee-based evidence for determining the factors of adoption of green finance in Nepal, the paper provides some insights in the growing literature of sustainable banking and practical implications for policymakers and banking institutions. Thus the study highlight that increasing employee’s awareness and expanding institutions initiative, strengthening the regulatory provisions and fostering positive behavioral intention can increase the adoption of green finance practices in Nepalese commercial banks.